Revitalizing the Social-Educational Role of Mosques in Fostering Pancasila Leadership Character among Early Childhood Learners in the Context of Quiet Quitting - Sapri Sapri; Sitti Aisyah Mu'min (Smart Society, 2026)
The rapid expansion of digital culture and increasing individualism among younger generations have contributed to the emergence of quiet quitting, a phenomenon characterized by declining social engagement, weakened collective responsibility, and reduced participation in community life. These challenges underscore the importance of strengthening character education from early childhood, particularly in rapidly urbanizing and multicultural settings such as Kendari City, Indonesia. This study aims to develop a conceptual understanding of how revitalizing the socio-educational functions of mosques can foster Pancasila leadership character among young children as a preventive foundation against future social disengagement associated with quiet quitting. This study employed an integrative literature review by synthesizing evidence from scholarly journal articles, academic books, policy documents, institutional reports, and official statistical publications published between 2018 and 2025. The selected literature was analyzed using thematic content analysis to identify and synthesize conceptual relationships among mosque-based education, Pancasila leadership, early childhood character development, and social engagement. The literature synthesis indicates that mosques possess substantial potential as community-based character education centers by facilitating the internalization of Pancasila leadership values, including religiosity, responsibility, cooperation, tolerance, discipline, and social concern through Qur'anic education, role modelling, collective social activities, community service, and children's active participation in religious and social programs. The synthesized evidence further suggests that strengthening the socio-educational functions of mosques may promote the development of socially responsible, community-oriented, and actively engaged future citizens while reducing the long-term risk of disengagement-oriented attitudes associated with quiet quitting. This study contributes to the literature by integrating the perspectives of quiet quitting, early childhood character education, Pancasila leadership, and mosque-based education into a unified conceptual framework that positions mosque revitalization as a community-based strategy for strengthening children's leadership character in the digital era.